2019
DOI: 10.1242/jeb.206383
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity joints and muscle groups in the human locomotor system alter mechanical functions to meet task demand

Abstract: To facilitate movement through mechanically complex environments, terrestrial animals have evolved locomotor systems capable of flexibly altering internal mechanics to meet external demands. They do this by shifting imposed workloads between joints/muscle groups (central mechanical flexibility) and/or by altering the function of individual joints/ muscle groups (local mechanical flexibility). In human locomotion research, central mechanical flexibility is well established and regularly reported. Local mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…From the previous researches (Cofré et al, 2011;Williams and Schache, 2016;Browne and Franz, 2018;Uematsu et al, 2018), ankle produces positive work during stance phase, which could be regarded as motor-like function. However, some studies regarded ankle as principle spring during walking (Lee et al, 2008;Qiao and Jindrich, 2016;Kuhman and Hurt, 2019). In this study, according to the functional behaviors and produced mechanical work of ankle during different phases, we show that ankle is dissipating mechanical energy during the first three phases (collision, rebound, and preload) and releasing mechanical energy during push-off.…”
Section: Ankle Contributes the Most During Push-off To Push Shank Faster During Walkingmentioning
confidence: 70%
See 2 more Smart Citations
“…From the previous researches (Cofré et al, 2011;Williams and Schache, 2016;Browne and Franz, 2018;Uematsu et al, 2018), ankle produces positive work during stance phase, which could be regarded as motor-like function. However, some studies regarded ankle as principle spring during walking (Lee et al, 2008;Qiao and Jindrich, 2016;Kuhman and Hurt, 2019). In this study, according to the functional behaviors and produced mechanical work of ankle during different phases, we show that ankle is dissipating mechanical energy during the first three phases (collision, rebound, and preload) and releasing mechanical energy during push-off.…”
Section: Ankle Contributes the Most During Push-off To Push Shank Faster During Walkingmentioning
confidence: 70%
“…Besides, slight changes occur in function indices with different walking speed. Kuhman and Hurt (2019) suggested that joints' functional behaviors during walking, especially for knee and ankle, were different under changed walking speed. The results in this study show that, strut function of knee during collision and push-off decreases with growing walking speed (seen in Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The voluntary production of movements in the neuromuscular system activates the nervous and locomotor systems to perform tasks [9]. Movement occurs due to the interaction of muscle tissue with bone tissue, with measures of lean mass being the determining factor for the execution of body movement [10]. Increased volume of lean mass is also identified as a significant characteristic for physical health and sports performance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3 ). If some of this negative work represents strain energy storage that will subsequently be returned, the toe brace resulted in a more damper-like midtarsal joint, with a higher ratio of negative to positive work [ 20 ]. The apparent increase in negative work looked to be primarily a result of a prolonged negative power phase and delayed transition to positive power.…”
Section: Discussionmentioning
confidence: 99%